2010
DOI: 10.1144/sp329.11
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and facies differentiation within a Middle Miocene carbonate platform, Ermenek, Mut Basin, southern Turkey

Abstract: In south-central Turkey, a carbonate platform system of early middle Miocene age is exposed in three-dimensional outcrops displaying a rich variety of carbonate facies associated with exceptionally well-preserved depositional geometries. This paper presents a detailed reconstruction of the geometries and facies organization across the prograding margin of one intra-platform carbonate bank that grew during the Langhian on the Ermenek Platform. The total thickness of the margin is approximately 250 m, and it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 43 publications
5
40
0
Order By: Relevance
“…The Miocene deeper marine deposits of the MutErmenek Basin (Köselerli Formation) were dated upper Burdigalian-Serravallian by using ostracods, planktonic foraminifera, and calcareous nannofossils (Tanar & Gökçen 1990;Atabey et al 2000). More recently, referring to the calcareous nannofossil biostratigraphy of Martini and Müller (1986), Bassant et al (2005) identified the upper part of the marine succession on the east side of the Mut Basin to be part of the NN5 biozone, whereas Janson et al (2010) identified in the uppermost strata of the Ermenek platform calcareous nannofossil assemblages of the NN6 biozone, confirming a Serravallian age for the topmost part of the Miocene marine deposits in the MutErmenek Basin.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The Miocene deeper marine deposits of the MutErmenek Basin (Köselerli Formation) were dated upper Burdigalian-Serravallian by using ostracods, planktonic foraminifera, and calcareous nannofossils (Tanar & Gökçen 1990;Atabey et al 2000). More recently, referring to the calcareous nannofossil biostratigraphy of Martini and Müller (1986), Bassant et al (2005) identified the upper part of the marine succession on the east side of the Mut Basin to be part of the NN5 biozone, whereas Janson et al (2010) identified in the uppermost strata of the Ermenek platform calcareous nannofossil assemblages of the NN6 biozone, confirming a Serravallian age for the topmost part of the Miocene marine deposits in the MutErmenek Basin.…”
Section: Introductionmentioning
confidence: 92%
“…In the Ermenek area, above a subtropical flat platform of late Burdigalian age (NN4), a platform-basin system developed during the Langhian (Janson et al 2010). At that time, a composite platform system developed to the NE of the town of Ermenek, including an aggradational barrier at the platform edge and several platform-banks prograding into intraplatform depression deposits.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations